A kind of adsorption material and its preparation method and application

By specific modification of chromium-containing metal organic frame materials, the electrostatic, hydrophobic and fluorine-fluorine interactions are enhanced, the problem of insufficient selectivity and adsorption capacity of existing adsorbents when removing PFOS in water is solved, and efficient and selective PFOS adsorption effect is achieved.

CN119591899BActive Publication Date: 2025-04-15THREE GORGES ENVIRONMENTAL TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510138332.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-15
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

Existing adsorbents lack selectivity and limited adsorption capacity when removing PFOS in water, making it difficult to effectively remove in complex environments.

Method used

The chromium-containing metal organic frame material is used and modified by specific modification groups to enhance the electrostatic interaction, hydrophobic action and fluorine-fluorine interaction of the adsorption material, thereby improving the adsorption performance and selectivity of PFOS.

Benefits of technology

It realizes efficient selective adsorption of PFOS in water, improves the specific surface area, pore size and stability of the adsorbed material, and significantly enhances its removal efficiency in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591899B_ABST
    Figure CN119591899B_ABST
Patent Text Reader

Abstract

The present invention provides an adsorption material and a preparation method and application thereof. The present invention relates to the technical field of metal organic framework materials. The adsorption material of the present invention comprises a chromium-containing metal organic framework, wherein the chromium-containing metal organic framework is grafted with a modifying group; the adsorption material has excellent adsorption efficiency for perfluorooctane sulfonic acid and its salt compounds in water, and achieves efficient and selective adsorption of PFOS.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal organic framework materials, and in particular to an adsorption material and a preparation method and application thereof. Background Art

[0002] Perfluorooctane sulfonyl compounds (PFOS) are composed of fully fluorinated anions in perfluorinated acidic sulfates and exist in salts, derivatives and polymers in the form of anions. PFOS is an organic pollutant that is difficult to decompose, with low volatility and high water solubility, and the water environment has become its main collection place. However, the traditional process design of sewage treatment plants mainly targets pollutants such as COD, BOD, nitrogen, and phosphorus, resulting in the inability to effectively remove PFOS and ultimately release it into environmental water bodies. Therefore, it is particularly important to study efficient treatment methods for PFOS in water.

[0003] In the field of wastewater and drinking water treatment, adsorption is widely used in pollutant removal due to its advantages such as simple operation, mature technology, and easy availability of raw materials. It is currently considered to be an effective technology suitable for removing PFOS from water. In recent years, a variety of adsorbents have been developed for the adsorption of PFOS, including activated carbon, biochar, nanocarbon materials, and clay minerals. However, these traditional adsorbents are usually effective against a variety of pollutants, lack selectivity for PFOS, and have difficulty in preferentially adsorbing PFOS in the presence of other competing compounds. In addition, traditional adsorbents such as granular activated carbon have limited adsorption capacity and are easily saturated.

[0004] Therefore, it is urgent to develop adsorbents with high adsorption capacity for the absorption of PFOS in water. Summary of the invention

[0005] The invention provides an adsorption material, which comprises a chromium-containing metal organic framework grafted with a specific modification group and has a high-efficiency adsorption capacity for PFOS in water.

[0006] The present invention also provides a method for preparing an adsorbent material. The method is simple to operate and can prepare an adsorbent material with a high-efficiency adsorption capacity for PFOS in water.

[0007] The present invention also provides a method for adsorbing perfluorooctane sulfonyl compounds. The method uses the above-mentioned adsorption material and can achieve efficient adsorption of perfluorooctane sulfonyl compounds.

[0008] In one aspect, the present invention provides an adsorption material, comprising a chromium-containing metal organic framework, wherein the chromium-containing metal organic framework is grafted with a modifying group, wherein the modifying group is as shown in Formula I;

[0009] Formula Ⅰ.

[0010] As described above for the adsorbent material, the organic ligand in the chromium-containing metal organic framework comprises terephthalic acid.

[0011] The adsorption material as described above has a surface with a positive charge of 33.5 mV.

[0012] The adsorbent material as described above has a contact angle of 103.4°.

[0013] The adsorbent material as described above has a specific surface area of ​​1025 m 2 · g –1 .

[0014] The adsorption material as described above has a pore size of 1.9 nm.

[0015] In another aspect, the present invention provides a method for preparing the adsorbent material as described above, comprising the following steps:

[0016] 1) reacting a chromium-containing metal organic framework with diethylenetriamine to obtain an amination intermediate;

[0017] 2) Under the action of an acid binding agent, the amination intermediate is reacted with trifluoromethanesulfonyl chloride to obtain the adsorption material.

[0018] In the preparation method described above, the mass ratio of diethylenetriamine to the chromium-containing metal organic framework is (4-6):1, and the mass ratio of trifluoromethanesulfonyl chloride to the amination intermediate is (1.2-1.6):1.

[0019] In the preparation method as described above, in step 1), the reaction temperature is 110°C;

[0020] And / or, in step 2), the reaction temperature is 20-30°C.

[0021] In another aspect, the present invention provides a method for adsorbing perfluoroalkyl compounds, using the adsorption material as described above or the adsorption material prepared by the preparation method as described above for adsorption treatment.

[0022] The adsorption material provided by the present invention includes a chromium-containing metal organic framework modified by a specific structural modification group. The chromium-containing metal organic framework has an adjustable mesoporous cage structure, a large specific surface area, excellent water stability and thermal stability, and the terminal water molecules of the trimerized Cr (III) octahedral cluster in its structure can be removed by heating to generate unsaturated metal sites, which is convenient for subsequent functional modification. After the chromium-containing metal organic framework is modified with the modification group shown in formula I, the adsorption performance and selectivity of PFOS can be significantly enhanced through electrostatic interaction, hydrophobic interaction and fluorine-fluorine interaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The synthetic route of the adsorption material provided in Example 1;

[0024] Figure 2 This is a scanning electron microscope test image of the adsorption material provided in Example 1 of the present invention;

[0025] Figure 3 XRD test spectrum of the adsorption material provided in Example 1 of the present invention;

[0026] Figure 4 A Fourier infrared spectrum of the adsorption material provided in Example 1 of the present invention;

[0027] Figure 5 This is the full XPS spectrum of the adsorption material provided in Example 1 of the present invention;

[0028] Figure 6 A bar graph showing the adsorption removal rate of PFOS by the adsorbent materials provided in Example 1 and Comparative Examples 1 and 2 of the present invention;

[0029] Figure 7 This is a bar graph showing the adsorption selectivity of the adsorbent material provided in Example 1 for PFOS. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Metal-organic framework (MOF) materials are a type of porous crystalline nanomaterials composed of metal ions and organic ligands, with advantages such as large specific surface area, adjustable pore size, and structural diversity. MOF materials are easy to synthesize, and MOFs with different physical and chemical properties can be constructed by adjusting the metal center or organic ligands. The adsorption performance can also be significantly enhanced by adding active sites or adjusting chemical properties through subsequent modification. These unique properties make MOF materials show great application potential in the adsorption and removal of pollutants.

[0032] Previous studies have shown that MOF materials have potential in removing PFOS, but their selectivity and adsorption performance still need to be improved, especially when used in complex environments, the material structure and functional properties need to be further optimized. Unmodified MOF materials can usually only rely on one or two interactions when adsorbing PFOS, such as electrostatic effects, hydrophobic effects, acid-base effects, or hydrogen bonds, which leads to low selectivity for PFAS and limited adsorption capacity. The selectivity can be effectively improved by introducing multiple interactions, but this requires careful design of the adsorbent structure.

[0033] In one aspect, the present invention provides an adsorption material, comprising a chromium-containing metal organic framework, wherein the chromium-containing metal organic framework is grafted with a modifying group, wherein the modifying group is as shown in Formula I;

[0034] Formula I.

[0035] The adsorption material provided by the present invention has excellent adsorption efficiency for PFOS in water, and realizes efficient and selective adsorption of PFOS. Among them, the chromium-containing metal organic framework has an adjustable mesoporous cage structure, a large specific surface area, excellent water stability and thermal stability, and the terminal water molecules of the trimerized Cr (III) octahedral cluster in its structure can be removed by heating, thereby generating unsaturated metal sites, which is convenient for subsequent functional modification, and the chromium-containing metal organic framework is modified with the modifying group shown in formula I, which can significantly enhance the adsorption performance and selectivity of PFOS through electrostatic interaction, hydrophobic interaction and fluorine-fluorine interaction at the same time.

[0036] The chromium-containing metal organic framework in the present invention refers to a porous material formed by chromium metal ions and organic ligands connected by coordination bonds. In the chromium-containing metal organic framework, the organic ligands can play a role in connecting metal nodes, thereby forming a three-dimensional network structure. In a specific embodiment, the organic ligands in the chromium-containing metal organic framework include terephthalic acid.

[0037] When the organic ligands in the chromium-containing metal-organic framework are of the above-mentioned type, they can not only coordinate with the chromium metal ions to form a stable framework structure, but also the above-mentioned type of organic ligands help to form regular pores. The adsorption performance and selectivity of the chromium-containing metal-organic framework can be adjusted by introducing substituents into the organic ligands.

[0038] The sulfonic acid groups contained in the PFOS molecular structure dissociate in water and exhibit negative charge. For the adsorbent material, the modified group contains an amino group, which can regulate the surface charge of the adsorbent material and make the adsorbent material positively charged. Under electrostatic interaction, the positively charged adsorbent material can better adsorb the negatively charged PFOS. The charge of the adsorbent material can also be regulated by controlling the proportion of the modified group in the adsorbent material.

[0039] In one embodiment, the surface of the adsorbent material has a positive charge of 33.5 mV.

[0040] Among them, the charge amount on the surface of the adsorbent material can be measured by Zeta potential analysis method.

[0041] When the surface of the adsorbent material carries a positive charge of 33.5 mV, it can not only effectively adsorb negatively charged PFOS molecules, but also more positive charges can improve the dispersion stability of the adsorbent material during the adsorption process, prevent particle aggregation between the adsorbent materials, and further improve the adsorption performance of the adsorbent material.

[0042] During the adsorption process of the adsorbent material, the hydrophilicity and hydrophobicity of the adsorbent material also affect the adsorption effect. In a specific embodiment, the contact angle of the adsorbent material is 103.4°.

[0043] The contact angle of the adsorbent material in the present invention refers to the contact angle formed by contact with water. The contact angle of the adsorbent material can be measured by a common method, for example, by using a contact angle measuring instrument to detect the adsorbent material.

[0044] When the contact angle of the adsorbent material is 103.4°, it indicates that the surface of the adsorbent material has a certain degree of hydrophobicity. On the one hand, the PFOS molecule has a hydrophobic carbon fluorine chain and a hydrophilic sulfonic acid group. The hydrophobicity of the adsorbent material surface is more likely to interact with the hydrophobic part of PFOS, thereby improving the adsorption capacity of the adsorbent material for PFOS. On the other hand, the hydrophobic adsorbent material can selectively adsorb hydrophobic pollutants in the water, such as PFOS, thereby improving the removal efficiency of PFOS in the water treatment process.

[0045] In one embodiment, the specific surface area of ​​the adsorbent material is 1025 m 2 ·g –1 .

[0046] The specific surface area of ​​the adsorption material can be measured by a common method in the art, such as a specific surface area analyzer.

[0047] When the specific surface area of ​​the adsorbent material is 1025 m 2 · g –1 This provides PFOS with an opportunity to fully contact the adsorption material, which helps to enhance the interaction between PFOS and the modified groups in the adsorption material, thereby improving the adsorption efficiency.

[0048] In one embodiment, the pore size of the adsorbent material is 1.9 nm.

[0049] The pore size of the adsorbent material in the present invention refers to the average pore size, which can be measured using common methods in the art.

[0050] The particle size of PFOS in water is about 1.1nm. When the pore size of the adsorbent material is 1.9nm, it can not only effectively adsorb and concentrate PFOS with a molecular size of 1.1nm, but also reduce the interference of other macromolecules on the adsorbent material through the size exclusion effect, improve the adsorption selectivity of the adsorbent material, avoid the adsorption sites being occupied by other macromolecules, and thus improve the adsorption efficiency.

[0051] In another aspect, the present invention provides a method for preparing the adsorbent material as described above, comprising the following steps:

[0052] 1) reacting a chromium-containing metal organic framework with diethylenetriamine to obtain an amination intermediate;

[0053] 2) Under the action of an acid-binding agent, the amination intermediate reacts with trifluoromethanesulfonyl chloride to obtain an adsorption material.

[0054] Specifically, the chromium-containing metal organic framework is dehydrated in a vacuum oven overnight to remove the terminal water molecules of the chromium octahedron and generate unsaturated metal sites, which are convenient for the subsequent grafting of the modification groups. Subsequently, the dehydrated chromium-containing metal organic framework is added to the first solvent to form a suspension, and diethylenetriamine is added to the suspension to mix evenly and react to obtain an amination intermediate.

[0055] A suitable first solvent, such as anhydrous toluene, may be selected according to actual conditions.

[0056] Among them, in order to increase the reaction rate, after adding diethylenetriamine, stirring and reflux can be carried out overnight under a nitrogen atmosphere. Subsequently, in order to separate the amino intermediate from the suspension, ion separation, washing, suction filtration, vacuum drying and the like can be used to obtain a relatively pure amination intermediate.

[0057] The present invention does not limit the preparation method of the chromium-containing metal organic framework. In a specific embodiment, the chromium-containing metal organic framework is prepared by a hydrothermal method using Cr(NO3)3·9H2O and terephthalic acid as precursors.

[0058] Surface amino functionalization was performed by selectively grafting diethylenetriamine onto the coordinatively unsaturated sites of the chromium-containing metal organic framework, which increased the positive charge of the material and thus enhanced the electrostatic attraction with the anionic PFOS.

[0059] Subsequently, the amination intermediate is reacted with trifluoromethanesulfonyl chloride under the action of an acid binding agent to obtain an adsorbent material.

[0060] In one specific embodiment, the amino intermediate and the acid binding agent are added to the second solvent, and trifluoromethanesulfonyl chloride is added dropwise after being mixed evenly. After reacting overnight, the mixture is washed by centrifugation and dried in vacuum to obtain an adsorbent material. In this process, the amino intermediate and trifluoromethanesulfonyl chloride are subjected to a sulfonylation reaction under a nitrogen environment to achieve fluorination of the amino intermediate, so that the chromium-containing metal organic framework is grafted with the group shown in Formula I.

[0061] A suitable acid-binding agent can be selected according to actual needs, as long as it can neutralize the acid generated during the reaction, such as triethylamine. A suitable second solvent can also be selected according to actual needs, such as N,N-dimethylformamide (DMF).

[0062] The preparation method provided by the present invention is simple to operate and can realize grafting of the modification group shown in formula I on the chromium-containing metal organic framework, and the obtained adsorption material has a high adsorption efficiency.

[0063] In one specific embodiment, the mass ratio of diethylenetriamine to the chromium-containing metal organic framework is (4-6):1, and the mass ratio of trifluoromethanesulfonyl chloride to the amination intermediate is (1.2-1.6):1.

[0064] In another specific embodiment, the mass ratio of diethylenetriamine to the chromium-containing metal organic framework is 5:1, and the mass ratio of trifluoromethanesulfonyl chloride to the amination intermediate is 1.4:1.

[0065] When the mass ratio of diethylenetriamine to the chromium-containing metal organic framework and the mass ratio of trifluoromethanesulfonyl chloride to the amino intermediate are within the above range, the grafting rate of the modified group can be effectively controlled, thereby regulating the adsorption performance of the adsorption material.

[0066] In one embodiment, in step 1), the reaction temperature is 110°C.

[0067] When the reaction temperature of step 1) is 110 degrees Celsius, not only the reaction rate can be increased, but also the selectivity of the reaction can be improved, which is beneficial to the formation of the amination intermediate and inhibits the occurrence of side reactions.

[0068] In another specific embodiment, in step 2), the reaction temperature is 20-30°C.

[0069] When the reaction temperature of step 2) is within the above range, the selectivity of the reaction can be improved, the chromium-containing metal organic framework can be effectively grafted with the modified groups, and the occurrence of side reactions can be avoided.

[0070] In another aspect, the present invention provides a method for adsorbing perfluoroalkyl compounds, using the adsorption material as described above or the adsorption material prepared by the preparation method as described above for adsorption treatment.

[0071] Since the adsorption method provided by the present invention adopts the above-mentioned adsorption material or the adsorption material prepared by the above-mentioned preparation method, it has excellent adsorption performance for perfluoroalkyl compounds.

[0072] The present invention does not limit the operation steps of the adsorption method, and conventional adsorption treatment operation steps in the art can be adopted.

[0073] The present invention is further described below through specific embodiments.

[0074] Example 1

[0075] The preparation method of the adsorption material provided in this embodiment comprises the following steps:

[0076] 1) A chromium-containing metal-organic framework (MIL-101(Cr)) was prepared by a hydrothermal method using Cr(NO3)3·9H2O and terephthalic acid as precursors.

[0077] 2) Weigh the chromium-containing metal organic framework and dehydrate it in a vacuum oven at 150 °C overnight. Then add the dehydrated chromium-containing metal organic framework into anhydrous toluene to form a uniform suspension. Then add diethylenetriamine (DETA) to the solution and mix well to obtain a mixed solution, in which the mass ratio of the chromium-containing metal organic framework to DETA is 5:1. Stir the mixed solution under reflux at 110 °C in a nitrogen atmosphere and react overnight. Centrifuge, wash with ethanol and deionized water for multiple times, and finally collect with ethanol by suction. Heat and dry in a vacuum oven to collect the amino intermediate, which is recorded as MIL-101-DETA.

[0078] 3) Add the amino intermediate and a trace amount of triethylamine (as an acid binder to neutralize the acid produced in the reaction) to DMF, mix well, stir at 25°C, and slowly add trifluoromethanesulfonyl chloride to prevent violent reaction. The ratio of trifluoromethanesulfonyl chloride to amino intermediate is 1.4:1, and the reaction is allowed to proceed overnight. Repeatedly centrifuge and wash the product with DMF and ethanol, and then dry it in a vacuum oven to obtain an adsorbent material, which is recorded as MIL-101-DETA-TF.

[0079] in, Figure 1 This is the synthesis route of the adsorption material provided in Example 1.

[0080] The adsorption material provided in Example 1 was tested by scanning electron microscope. Figure 2 As shown in the image, the crystal morphology of the adsorbent material is a flat surface, clear-cut octahedral morphology with an average size of 300 nm. This morphology is similar to that of the original chromium-containing metal organic framework, indicating that the overall morphology of the material remains unchanged during the functionalization process.

[0081] The adsorbent material provided in Example 1 was subjected to XRD test, Fourier transform infrared spectroscopy test and XPS test. XRD analysis further confirmed the crystal structure of the adsorbent material, such as Figure 3 As shown in the figure, its diffraction peaks match the characteristic peaks of the chromium-containing metal-organic framework and the simulated chromium-containing metal-organic framework, indicating the successful synthesis of the chromium-containing metal-organic framework and the crystal structure of the chromium-containing metal-organic framework remains intact during the functional modification process. The results of the Fourier infrared spectrum are shown in Figure 4 As shown, the adsorbed material has the peaks at 1617 and 1399 cm -1 Two strong absorption peaks were observed at 3500~3200cm, corresponding to the asymmetric and symmetric stretching vibrations of the carboxyl group, which are consistent with the characteristic peaks of the chromium-containing metal organic framework. -1 Between and 813cm -1 New peaks appeared on the left and right, which were attributed to the stretching vibration and deformation vibration of NH, indicating the successful introduction of amino groups. The composition of the modified groups was further verified by XPS analysis, such as Figure 5 As shown, the full XPS spectrum shows that the adsorbed material has the same C1s, O1s and Cr2p peaks as the chromium-containing metal organic framework, and new N1s and F1s peaks appear, indicating the successful grafting of the modifying group.

[0082] Comparative Example 1

[0083] The preparation method of the adsorption material provided in this comparative example comprises the following steps:

[0084] A chromium-containing metal organic framework was prepared by a hydrothermal method using Cr(NO3)3·9H2O and terephthalic acid as precursors. The chromium-containing metal organic framework was the adsorption material and was recorded as MIL-101 (Cr).

[0085] Comparative Example 2

[0086] The preparation method of the adsorption material provided in this comparative example comprises the following steps:

[0087] 1) A chromium-containing metal-organic framework (MIL-101(Cr)) was prepared by a hydrothermal method using Cr(NO3)3·9H2O and terephthalic acid as precursors.

[0088] 2) Weigh the chromium-containing metal organic framework and dehydrate it in a vacuum oven at 150 °C overnight. Then add the dehydrated chromium-containing metal organic framework into anhydrous toluene to form a uniform suspension. Then add diethylenetriamine (DETA) to the solution and mix well to obtain a mixed solution, in which the mass ratio of the chromium-containing metal organic framework to DETA is 5:1. Stir and reflux the mixed solution under a nitrogen atmosphere at 110 °C overnight. Centrifuge, wash with ethanol and deionized water for multiple times, and finally collect with ethanol by suction. Heat and dry in a vacuum oven to collect the amino intermediate, which is the adsorption material, recorded as MIL-101-DETA.

[0089] Test Case

[0090] 1) Surface property test

[0091] The grafting rate, surface charge, contact angle, specific surface area, pore size, etc. of the adsorption materials provided in all embodiments are tested, comprising the following steps:

[0092] The surface electric potential was tested by using a nano-particle size potential analyzer using Zeta potential analysis;

[0093] The contact angle was tested using a contact angle measuring instrument.

[0094] The BET specific surface area and pore size distribution of the adsorbent material were determined by the nitrogen adsorption / desorption isotherms obtained by a specific surface area analyzer at -196 °C. The specific results are shown in Table 1.

[0095] Table 1

[0096]

[0097] 2) Adsorption performance test

[0098] The adsorption test was carried out at room temperature and 150 rpm on a shaker. 50 mL of the adsorbent materials provided in the examples and comparative examples (5 mg each) were added to a 50 mg / L –1 PFOS solution, and adjust the solution pH to 5.0 by adding NaOH or HCl. After shaking for 2 hours, separate the solid and supernatant in the solution, and collect them for subsequent testing, test the PFOS solution before and after the adsorption test, and determine the PFOS content in the PFOS solution before and after the adsorption test. Adsorption removal rate = (content before adsorption test - content after adsorption test) / content before adsorption test × 100%. The specific test results are shown in Table 2.

[0099] in Figure 6 The adsorption removal rate of PFOS by the adsorbent material provided in Example 1 and Comparative Example 1 and Comparative Example 2 is as follows: Figure 5It can be seen that the adsorption rate of PFOS by the adsorbent material provided in Example 1 is significantly higher than that of the adsorbent materials provided in Comparative Examples 1 and 2.

[0100] Figure 7 This is a bar graph of the adsorption selectivity of the adsorbent material provided in Example 1 for PFOS. The results show that the adsorption rate of the adsorbent material provided in Example 1 for PFOS is significantly stronger than that of substances with similar structures or properties such as octanoic acid (OA), octane sulfone (OS) and cetyltrimethylammonium bromide (CTAB), showing its excellent selectivity for PFOS, which indicates that the adsorbent material provided by the present invention can achieve efficient and selective adsorption of PFOS.

[0101] Table 2

[0102]

[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An adsorption material, characterized in that: It includes a chromium-containing metal organic framework, wherein the chromium-containing metal organic framework is grafted with a modifying group, and the modifying group is as shown in formula I; Formula Ⅰ.

2. The adsorption material according to claim 1, characterized in that The organic ligands in the chromium-containing metal-organic framework include terephthalic acid.

3. The adsorption material according to claim 1 or 2, characterized in that: The surface of the adsorption material has a positive charge of 33.5 mV.

4. The adsorption material according to claim 1 or 2, characterized in that: The contact angle of the adsorbent material is 103.4°.

5. The adsorption material according to claim 1 or 2, characterized in that: The specific surface area of ​​the adsorption material is 1025m 2 ·g –1 .

6. The adsorption material according to claim 1 or 2, characterized in that: The pore size of the adsorption material is 1.9 nm.

7. A method for preparing the adsorption material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) reacting a chromium-containing metal organic framework with diethylenetriamine to obtain an amination intermediate; 2) Under the action of an acid binding agent, the amination intermediate is reacted with trifluoromethanesulfonyl chloride to obtain the adsorption material.

8. The preparation method according to claim 7, characterized in that: The mass ratio of diethylenetriamine to the chromium-containing metal organic framework is (4-6):1, and the mass ratio of trifluoromethanesulfonyl chloride to the amination intermediate is (1.2-1.6):

1.

9. The preparation method according to claim 7 or 8, characterized in that: In step 1), the reaction temperature is 110°C; And / or, in step 2), the reaction temperature is 20-30°C.

10. A method for adsorbing a perfluorooctane sulfonyl compound, characterized in that: Adsorption treatment is performed using the adsorption material described in any one of claims 1 to 6 or the adsorption material prepared by the preparation method described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation and novel application of a type of MIL-101(Cr) adsorbent modified by virtue of post translation

    CN105107467A

  • Synthesis method for fluorine-containing polyethyleneimine

    CN110467540A